Pramipexole versus dual release levodopa in restless legs syndrome: a double blind, randomised, cross-over trial (Swiss Medical Weekly, 2011)
QUESTIONS UNDER STUDY: To compare efficacy and safety of the dopamine agonist pramipexole (PPX) versus reference treatment with dual release levodopa/benserazide (L/B) in denovo patients with restless legs syndrome (RLS). METHODS: A total of 39 men and women between 25 and 85 years old, fulfilling all clinical criteria for diagnosis of idiopathic RLS, previously untreated, participated. The study was performed as a randomised, double-blind, double-dummy crossover trial with two treatment periods of four weeks and took place in six Swiss certified sleep-centres. Interventions were PPX 0.25–0.75 mg and dual-release L/B 125–375 mg. The primary outcome measure was the frequency of periodic limb movements while in bed (PLM index, PLMI). Secondary endpoints included the changes in patient ratings on the International RLS Study Group Rating Scale (IRLS). RESULTS: Both pramipexole and dual-release L/B were effective in reducing PLM and RLS symptoms. Mean PLMI reduction was –11.5 for PPX and –7.7 for L/B (baseline 21.1 and 21.5), and the mean IRLS score reduction was –7.2 and –4.0 (baseline 20.8 and 21.1). In patients with an IRLS score >20 (38%), a significantly (p = 0.047) higher PLMI reduction for PPX (-8.5), as compared to L/B (–4.3), was found. A higher incidence of “augmentations” and “involuntary movements” for L/B, and “nausea or vomiting” and “hypotension with dizziness” for PPX treatment were noted as adverse effects. CONCLUSION: This study showed comparable effects of PPX versus dual-release L/B for short-term treatment of denovo patients with mild to moderate RLS.